Genomic survey of SARS-CoV-2 vaccine breakthrough infections in healthcare workers from Kerala, India. Issue 2 (August 2021) - Philomina J, Beena; Jolly, Bani; John, Neethu; Bhoyar, Rahul C.; Majeed, Nisha; Senthivel, Vigneshwar; CP, Fairoz; Rophina, Mercy; Vasudevan, Bindhu; Imran, Mohamed; Viswanathan, Prasanth; Arvinden, V.R.; et al.
Highlights: All 6 patients presented with symptomatic COVID-19 breakthrough infection. 2 patients were infected despite the presence of SARS-CoV-2 antibodies. 4 fully vaccinated patients were infected with B.1.1.7 variant of SARS-CoV-2. Spike variants E484K and S477N were found in SARS-CoV-2 isolates from 2 patients. None of the patients presented with severe disease or required hospitalization.